ECONOMIC PERFORMANCE OF MANGROVE CRAB FISHERY BUSINESS IN MOJO MANGROVE ECOSYSTEM AREA, PEMALANG REGENCY, CENTRAL JAVA, INDONESIA - Trisnani D Hapsari; Azis N Bambang; Abdul Ghofar; Aristi D. P. Fitri; Luky Adrianto (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2022)
The mangrove ecosystem in the Mojo Village Coastal Area, Pemalang Regency, Central Java Province is one of the potential sources of mangrove crabs. The high market demand has led to overexploitation as indicated by a decrease in catch and a decrease in the average size caught. The fishing of mangrove crabs in the Mojo Mangrove Ecosystem, Pemalang Regency can be caught any time, depending on the type of fishing gear used. The fishing gear used includes scoop nets, folding traps (local term: bubu), fishing rods, and trammel nets. The reduction in the production of ma0ngrove crabs and the decrease in the average size caught can lead to a decline in fishermen’s income. This study aims to examine the economic performance of the mangrove crab fishery business in the Mojo Coastal Area and assess the feasibility of the business. The research method used was a survey method. Data analysis included profit analysis, revenue cost ratio (R/C ratio), Return of Investment (ROI) and Payback period (PP). The results show that the mangrove crab business both catching and farming are known to be still profitable to do. Folding traps (bubu) fishermen who operate the fishing gears at sea earned the highest net income, i.e. an average of IDR 5,127,451/month. The highest value of R/C ratio was in catching mangrove crabs using fishing rods, which was 3.9. The highest ROI value (11,294%) and the fastest return are found in investment on crab fishing activities using a scoop net, with a payback period of 3 days. Soft shell crab farming is economically feasible to be continued with an average profit of IDR 8,150,125/month, R/C value of 1.22, Payback Period was 2 years 2 months and 242% ROI.